Atypical presentation of patients with chronic myeloid leukemia in chronic phase—Case report - Ramdohr, Florian; Fabarius, Alice; Maier, Bettina; Bretschneider, Daniela; Jauch, Anna; Monecke, Astrid; Metzeler, Klaus H.; Janssen, Johannes W. G.; Schlenk, Richard F.; Kayser, Sabine (Frontiers in Oncology, 2022)
The presence of the translocation t(9;22)(q34;q11), leading to the BCR::ABL1 fusion transcript is the hallmark of chronic myeloid leukemia (CML). Nevertheless, atypical presentation at diagnosis can be challenging. However, although most patients with CML are diagnosed with the e13a2 or e14a2 BCR::ABL1 fusion transcripts, about 5% of them carry rare BCR::ABL1 fusion transcripts, such as e19a2, e8a2, e13a3, e14a3, e1a3 and e6a2. In particular, the e6a2 fusion transcript has been associated with clinically aggressive disease frequently presenting in accelerated or blast crisis phases. To date, there is limited evidence on the efficacy of front-line second-generation tyrosine kinase inhibitors for this genotype. Here, we report two patients, in whom the diagnosis of CML was challenging. The use of primers recognizing more distant exons from the common BCR::ABL1 breakpoint region correctly identified the atypical BCR::ABL1 e6a2 fusion transcript. Treatment with second-generation tyrosine kinase inhibitor nilotinib was effective in our patient expressing the atypical e6a2 BCR::ABL1 fusion transcript.